Final overall survival results of WJTOG3405, a randomized phase III trial comparing gefitinib versus cisplatin with docetaxel as the first-line treatment for patients with stage IIIB/IV or postoperative recurrent EGFR mutation-positive non-small-cell lung cancer. (25th September 2019) - Yoshioka, H; Shimokawa, M; Seto, T; Morita, S; Yatabe, Y; Okamoto, I; Tsurutani, J; Satouchi, M; Hirashima, T; Atagi, S; Shibata, K; Saito, H; et al.
Abstract: Background: Primary analysis of the phase III study WJTOG 3405 demonstrated superiority of progression-free survival (PFS) for gefitinib (G) in patients treated with the epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) gefitinib compared with cisplatin plus docetaxel (CD) as the first-line treatment of stage IIIB/IV or postoperative recurrent EGFR mutation-positive non-small-cell lung cancer. This report presents final overall survival (OS) data. Patients and methods: Patients were randomized between G (250 mg/day orally) and cisplatin (80 mg/m 2 intravenously) plus docetaxel (60 mg/m 2 i.v.), administered every 21 days for three to six cycles. After the exclusion of 5 patients, 172 patients (86 in each group, modified intention-to-treat population) were included in the survival analysis. OS was re-evaluated using updated data (data cutoff, 30 September 2013; median follow-up time 59.1 months). The Kaplan–Meier method and the log-rank test were used for analysis, and hazard ratios (HRs) for death were calculated using the Cox proportional hazards model. Results: OS events in the G group and CD group were 68 (79.1%) out of 86 and 59 (68.6%) out of 86, respectively. Median survival time for G and CD were 34.9 and 37.3 months, respectively, with an HR of 1.252 [95% confidence interval (CI): 0.883–1.775, P  = 0.2070]. Multivariate analysis identified postoperative recurrence and stage IIIB/IV disease as independent prognostic factors, with an HR of 0.459 (95% CI: 0.312–0.673, P  <   0.001). Median survival time (postoperative recurrence versus stage IIIB/IV disease) were 44.5 and 27.5 months in the G group and 45.5 and 32.8 months in the CD group, respectively. Conclusion: G did not show OS benefits over CD as the first-line treatment. OS of patients with postoperative recurrence was better than that of stage IIIB/IV disease, even though both groups had metastatic disease. This study was registered with UMIN (University Hospital Medical Information Network in Japan), number 000000539.